Understanding the effect of surface flaws on fracture of silicon die - Punzalan, Jaime Jr. C.
An integrated circuit (IC) silicon die experiences different thermomechanical stresses during assembly, test, mounting and application. Ideally, the silicon dice is expected to withstand stresses induced during normal processing and application. But it is not uncommon for standard assembled package and flip chip package to fail due to silicon die cracking. As the industry continues to develop smaller and thinner silicon dice to fit the ever shrinking IC unit, understanding of the failure mechanism becomes more important.